The content and access dynamics of a busy Web site findings and implications. - Padmanabhan, Venkata N. (Computer communication review.)
In this paper, we study the dynamics of the MSNBC news site, one of the busiest Web sites in the Internet today. Unlike many other efforts that have analyzed client accesses as seen by proxies, we focus on the server end. We analyze the dynamics of both the server content and client accesses made to the server. The former considers the content creation and modification process while the latter considers page popularity and locality in client accesses. Some of our key results are: (a) files tend to change little when they are modified, (b) a small set of files tends to get modified repeatedly, (c) file popularity follows a Zipf-like distribution with a parameter &agr that is much larger than reported in previous, proxy-based studies, and (d) there is significant temporal stability in file popularity but not much stability in the domains from which clients access the popular content. We discuss the implications of these findings for techniques such as Web caching (including cache consistency algorithms), and prefetching or server-based ``push'' of Web content.